EFFECT OF ETHANOL EXTRACT OF ACORUS CALAMUS ON PYRUVATE KINASE AND PHOSPHOENOLPYRUVATE CARBOXYKINASE ACTIVITY OF COTYLOPHORON COTYLOPHORUM - R. LOKESH; L.VEERAKUMARI (International Journal of Pharma and Bio Sciences, 2016)
Cotylophoron cotylophorum is a ruminant parasite which causes the disease paramphistomosis in livestock. Immature flukes cause heavy infection resulting in foul-smelling diarrhoea, dehydration and death of the animal. Effect of ethanol extract of Acorus calamus on pyruvate kinase and phosphoenolpyruvate carboxykinase activity of Cotylophoron cotylophorum was studied in the present investigation. The parasites were exposed to various sub lethal concentrations of ethanol extract of Acorus calamus for 2h, 4h and 8h. Following the method of MCmanus and Smyth, pyruvate kinase and phosphoenolpyruvate carboxykinase were assayed. Maximum level of inhibition in pyruvate kinase and phosphoenolpyruvate carboxykinase activities was observed after 8h of incubation at 0.1 mg ml-1 concentration. Inhibition of pyruvate kinase and phosphoenolpyruvate carboxykinase may impair the phosphoenolpyruvate-succinate pathway and reduces the synthesis of ATP. Decreased generation of ATP may impair energy dependent physiological activities of the parasite and thereby eliminating the parasite from the host.